Dynamic instability of a wind turbine blade due to large deflections - Lopez-Lopez, Andres (Strojniški vestnik, 2020)
Wind turbine blades are designed to be thin and flexible elements. Because unstable dynamic behaviour can affect the life of the rotor, it is crucial to understand the instability of non-linear behaviour caused by large deflections. The present study undertakes both a stability analysis of the non-linear response and an experimental validation of a simplified model for a wind turbine blade based on a cantilever beam. The model is formulated taking into account large geometric deflections and assuming a Galerkin approach. The model is validated experimentally in a wind tunnel with aluminium beams of differing geometry. Analysis of the dynamic response using phase planes reveals that the degree of instability is related to the amplitude of the excitation and the stiffness characteristics.
Keywords: fazna ravnina; instability; large deflection; lopatica vetrne turbine; nelinearen model; nelinearne vibracije; nestabilnosti; non-linear model; phase planes; velik odklon; vetrovnik; wind turbine blade